MENDIDIK ANAK SUPERNORMAL DALAM PERSPEKTIF PENDIDIKAN ISLAM: MENDIDIK ANAK SUPERNORMAL - Muhammad Wisnu Khumaidi; Muhammad Ari Wibowo; Masfiatul Asriyah (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2019)
In the current era of globalization, the world feels increasingly narrow. The progress of science and technology is rapidly increasing which has various impacts in all fields of human life. Both positive and negative impacts. Quality human resources are the overall development of humans. Quality human beings are humans who develop optimally both physically, cognitively, emotionally, socially and spiritually. The Indonesian people have superior sources that can be used as high quality human resources. These superior sources are children who have higher intelligence or can be called supernormal children. The advantages possessed by supernormal children are important to be developed and guided. Because children who have intelligence are more like plants that need someone who can guide and help them to develop naturally, eliminate various obstacles that are in front of him, and pave the way for him. They also need someone who can understand and appreciate their strengths. If supernormal children are not provided with educational services, are not mentored and are not educated according to their specific needs, so that their potentials cannot be realized, in addition to losing superior seeds for the development of the Indonesian nation, these children can be disadvantaged and can even be a problem child, and could drop out of school. It is clear that supernormal children need special and serious education and guidance. In order for the balance and happiness of life in the world and the hereafter to supernormal children, it needs to be guided with ahlakul kharimah because it is in the content of quality education. Supernormal children are a wealth of human resources that are not measured in value.